Comparative use of anodic oxidation, electro-Fenton and photoelectro-Fenton with Pt or boron-doped diamond anode to decolorize and mineralize Malachite Green oxalate dye. (10th November 2015) - El-Ghenymy, Abdellatif; Centellas, Francesc; Rodríguez, Rosa María; Cabot, Pere Lluís; Garrido, José Antonio; Sirés, Ignasi; Brillas, Enric
Highlights: Degradation of Malachite Green oxalate solutions at pH 3.0 by AO, AO-H2 O2, EF and PEF. A Pt anode leads to slower decolorization and mineralization than BDD. Up to 97% mineralization by the most powerful PEF process with BDD at 100 mA cm −2 . Study of the evolution of seven final short-chain aliphatic carboxylic acids. Conversion of the initial N atoms of the dye mainly into NH4 +, along with small amounts of NO3 − . Abstract: The degradation of 100 cm 3 of 177 mg dm −3 of the triphenylmethane dye Malachite Green oxalate at pH 3.0 was studied by anodic oxidation with stainless steel cathode (AO-SS), AO with air-diffusion cathode (AO-H2 O2 ), electro-Fenton (EF) and photoelectro-Fenton (PEF) with UVA light. The main oxidizing species were hydroxyl radicals formed from either water oxidation at the anode surface or in the bulk between added Fe 2+ and H2 O2 generated at the air-diffusion cathode. The use of a Pt anode led to slower decolorization and mineralization than BDD in all treatments because of the higher oxidation power of the latter. The decolorization was much faster for EF and PEF compared to AO-SS and AO-H2 O2 due to the contribution of hydroxyl radicals in the bulk. PEF allowed the quickest color removal by the rapid Fe 2+ regeneration from the photolysis of Fe(III) complexes with oxalate. The most powerful process was PEF with BDD, which yielded total decolorization in 6 min and 97% mineralization at 240 min operating at 100 mA cm −2, thanks to hydroxyl radicals formed at the anode surface and in the bulk along with the photolytic action of UVA radiation. The evolution of final carboxylic acids like maleic, fumaric, succinic, acetic, oxalic, formic and oxamic was followed by ion-exclusion HPLC. All these acids and their Fe(III) complexes were removed more slowly with Pt anode. The initial N atoms of the dye were pre-eminently accumulated as NH4 + ion, along with small amounts of NO3 − ion.